Changes in the Perception of Ground Beef Quality as a Result of Price Per Pound Labeling - E. S. Beyer; K. M. Harr; K. J. Farmer; S. G. Davis; M. D. Chao; J. L. Vipham; M. D. Zumbaugh; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:The objective of this study was to determine the effect of perceived palatability on ground beef patties by providing consumers with differing price per pound labels. Study Description:Ground beef chubs (n = 15)of 80% lean/20% fat composition were used for all samples. Patties were formed 11 days after processing into 0.25 lb patties using a commercial patty former. Samples were cooked to 160°F and served to consumers to determine different quality attributes. Consumers were given the following prices for each sample: Ultra-High - $6.25/lb; High - $5.00/lb; Medium - $3.75/lb; Low - $2.50/lb; Ultra-Low - $1.25/lb or no information provided (NONE). Bottom Line:Based on this research, consumer’s quality perception is affected by price variations, but not the willingness to purchase, indicating consumers are not willing to pay more for ground beef even with an improved eating experience.
Keywords: ground beef; labeling; palatability